Tugas Dan Tanggung Jawab Kepala Sekolah Menuju Tertib Administrasi Pendidikan Yang Efisien dan Produktif - Hasibuan, Eka Damayanti; Nur Rizkiya Makhfiro Nst,; Siregar, Diana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This journal discusses the key role of the principal in creating and maintaining efficient and productive educational administration at Ummi Fatimah Kindergarten. Good educational administration is very important in achieving the goals of quality education. The principal has the main duties and responsibilities in ensuring that all aspects of administration run well and effectively. This article provides an overview of the duties and responsibilities of school principals in achieving this goal. A qualitative approach was used to gain an in-depth understanding of the duties and responsibilities of school principals. The case study at Ummi Fatimah Kindergarten involved direct observation, interviews with the school principal, and analysis of documents related to educational administration. The collected data was analyzed descriptively to identify main themes. The results of the study show that school principals play a key role in managing teaching plans, supervising learning activities, managing human resources, financial administration, and infrastructure. By understanding and carrying out these duties and responsibilities well, school principals can help create an efficient and productive educational environment, which in turn will provide great benefits for early childhood development.